Approximation method in problems of potential theory - Sinaiskii, E. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the properties of the Dzyadyk approximation method in the case of a binomial function. We study conditions under which an estimate for the relative error of approximation in the uniform metric is exact. The results obtained are applied to certain problems in potential theory.